Unintended effects of health advertising to women - Shoebridge, Andrea; O'Ferrall, I.; Howat, Peter; Mitchell, Helen (Australian Health Promotion Association, 2003)
Issue addressed: The images and values used by health advertising may produce counter outcomes to those intended. Methods: Three age cohorts (11-12, 14-15 and 18-25 years old) of girls and young women, sampled from low, medium and high socio-economic status backgrounds, were asked about the content of televised commercial and public health advertising to women. Transcripts of group discussions and follow-up interviews were thematically analysed. Results: Clear age-related cognitive and attitudinal differences, grouped into values and audience segmentation fit, were found. However, poor self-comparisons with advertising models, failure to identify with content, and adoption of dominant health values were common to all. The use of high-value visual imagery was paradoxically supported and rejected as were the overt health messages in the advertising. Conclusions: There is a wide range of responses to health advertising material related to social contexts and diverse experience. Some of these responses may bring unintended effects for individuals in both target and general audiences.